On philosophy of age. Fractal structure of life and periodic table of ages - Epstein, M. N. (Bi͡u︡lletenʹ Sibirskoĭ medit͡s︡iny, 2006)
The article represents the fractal age theory, where the terminology of nonlinear dynamics (synergetic) obtains figural sense.